Influência da incorporação de argila e tecidos de fibra de juta (Corchorus capsularis) nas propriedades mecânicas e de flamabilidade de compósitos poliméricos - AZEVEDO, Amanda Chaves de (2019)
Concern for the environment in society generates several studies aiming to replace materials that already exist with others that have less impact on the environment. In view of this, natural fibers are good substitutes for reinforcements in polymeric matrix composite materials. Clay has as its main characteristics the fact that it is a natural material that is easily found and that has interesting granulometry to study. The objective of this work is based on the manufacture of polymeric matrix composite materials with the incorporation of jute fiber and clay fabric for verification of physical, mechanical and flame retardant properties. Isophthalic polyester matrix composite materials were produced with jute fiber and clay fabric (100 mesh). The method used to do the composite plates was the hand lay up. The isophthalic polyester resin was used with 1.5 % (v/v) cobalt accelerator and 1.0 % (v/v) catalyst. Clay was used in proportions of 0 %, 5 %, 15 % and 25 % by mass. A layer of jute tissue was used. X-ray diffraction was performed to evaluation of clay mineralogical compositions. For the composites physical tests of apparent specific mass, apparent porosity and water absorption were performed using NBR 12766. Tests were also performed to verify tensile strength (ASTM D3039 standart) and flexural strength (ASTM D790 standard) of the specimens, as well as analysis of the fracture surface by Scanning Electron Microscopy (SEM). Was performed the flame retardation (ASTM D635 standard). Physical tests showed an increase in apparent specific mass. There was an increase in the composites resistance with clay and also with the jute, in relation to the full matrix. The best tensile strength result found was 23.05 MPa, related to clay-only composites. For the flexure test the highest result was 75.86 MPa, which was also for clay-only composites. In the fracture surface analysis (by SEM) it was observed good dispersion of the particulate in clay composites and some voids, in the jute fiber fabric composites it was observed voids, fibers arranged transversely to loading and difficulty of wettability of resin in fiber. The flammability test showed that the lowest burn rate recorded was 16.79 mm / min. The results demonstrated good mechanical and flame retardant characteristics for the composites.